(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate and compare the hypolipidemic and hepatoprotective effects of Zingiber officinale (ginger), Trigonella faenumgraecum (Methi) and Allium sativum (Garlic) in hypercholesterolemic animal model ( albino rats) in comparison with 3-hydroxy 3- methyl glutaryl Co A reductase inhibitor (Atorvastatin) Study Design: Experimental study. Pace and Duration of Study: This study was conducted at Biochemistry Department, Al Tibri Medical College, Isra University, Karachi Campus from January 2016 to December 2016. Materials and Methods: Thirty six albino rats (wistar strains) of both gender were taken and divided into six groups namely (A) Normal control (B) Hypercholesterolemic (C) Zingiber 5% (D) Fenugreek 5%, (E) Allium sativum 5% supplemented groups and (F) Atorvastatin supplemented group. The blood was analyzed for lipid profile and serum liver enzymes after 8 weeks of supplementation. Results: The serum cholesterol, LDL-C, triacylglycerol,Alanine aminotransferase (ALT), Aspartate amino-transferase (AST) and Alkaline phosphatase (ALP) were increased in hypercholesterolemic rats as compared to normal control rats. Zingiber officinale, Fenugreek and Allium sativum supplemented groups, when compared with hypercholesterolemic group showed lowering of lipid profile and also lowering of serum liver enzyme activities. Zingiber officinale, Fenugreek and Allium sativum supplemented rats had shown no significant difference in the serum level of total cholesterol, HDL- C, LDL-C among the three groups. The triacylglycerol level was markedly decreased in Zingiber officinale supplemented group as compared with Atorvastatin supplemented group. ALT, AST level had shown no significant difference in Zingiber officinale supplemented group as compared to Atorvastatin supplemented rats. Conclusion: The data obtained from this study concluded that the Zingiber officinale, Fenugreek and Allium sativum had shown the preventive role in hyperlipidemia. Zingiber oficinale is more effective in lowering serum triacylglycerol level and also potent hepatoprotective effect as compared to Fenugreek, Allium sativum and Drug Atorvastatin.